Effect of Ethephon (2-chloroethylphosphonic acid) on leaves, flowering, fruiting and seed of local Jatropha curcas L. / Rosatikah Rosli, Abdul Rashid Said Asghar and Najihah Farhan Sabri - Rosli, Rosatikah; Said Asghar, Abdul Rashid; Farhan Sabri, Najihah (Universiti Teknologi MARA, Perlis, 2012)
As a potential petro-diesel substitute, low number of fruit production becomes the main constrain to develop J. curcas as a second plant oil source after palm oil in Malaysia. Utilization of plant growth regulators has been scientifically proven to increase plant growth under certain concentrations. This study was conducted to investigate the effect of different concentrations of ethephon on leaves, flowering, fruit size and number of fruit seed of J. curcas. Different concentration of ethephon (0 mg L-1, 150 mg L-1, 300 mg L-1 and 600 mg L-1) was sprayed once on foliar. Application of ethephon induced leaves discoloration and necrosis 24 hours after treatment. Number of leaves on plant extremely reduced in 72 hours. All ethephon treated plant fastened flower buds production, approximately 15 days in average after shoot emergence. Highest concentration (600 mg L-1) reduced 26.95% flower stalk compared to control. 150 mg L-1 and 300 mg L-1 promoted female flower up to 8.4 compared to control. 300 mg L-1 of ethephon reduced 32.6% number of fruit and 20.54% number of seed, while 150 mg L-1 slightly increase 8.4% of fruit size compared to control. Ethephon has potential in promoting flower buds and increasing number of female flowers in J. curcas but not an effective growth regulator in increasing number of fruits.